Макарычев ответы алгебра 7 класс решебник

Номер 794

Условие:

Докажите, что:
а) а(х + 6) + х(х - 3а) = 9 при х = 2а - 3;
б) х(х - За) + а(а + х) + 4 = 13 при х = а + 3.

 

Ответ:

a) а • (х + 6) + х • (х - 3а) при x = 2a - 3 => a • (2a - 3 + 6) + (2a - 3)(2a - 3 - 3a) = a • (2a + 3) + (2a - 3)(-a - 3) =
= 2a2 + 3a - 2a2 - 6a + 3a + 9 = 9;

6) х • (х - За) + а • (а + х) + 4 при х = a + 3 => (a + 3)(a + 3 - 3a) + a • (a + a + 3) + 4 =
(a + 3)(3 - 2a) + a • (2a + 3) + 4 = 3a - 2a2 + 9 - 6a + 2a2 + 3a + 4 = 9 + 4 = 13.

share with Whatsapp
share with Telegram
powered by social2s